2018
DOI: 10.7759/cureus.3030
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Atherogenic Risk of Lipoprotein(a) in Type 2 Diabetic Patients

Abstract: Type 2 diabetes mellitus (T2DM) has high morbidity and results in increased risk of mortality mainly due to cardiovascular diseases. Different factors have been found to be responsible for the increased prevalence of coronary artery disease (CAD) in T2DM. One of these factors includes raised serum levels of lipoprotein(a) (Lp(a)). The present study was designed to evaluate the association of Lp(a) levels with T2DM in Libyan patients and find the degree of association between Lp(a), glycemic control, insulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Some other stud-ies showed that CRP and IL-6 levels correlated with significance positively with Lp(a) levels in hemodialysis patients [16]. Lp(a) levels showed no significant correlations with glycemic control parameters nor insulin and triglyceride levels in study with diabetic patients [17]. Some authors suggest that levels of hsCRP are associated with a disorders of lipid profile such as an increase in total cholesterol, triglycerides and LDL cholesterol and lower HDL-but the mechanism is not entirely clear [18].…”
Section: Discussionmentioning
confidence: 83%
“…Some other stud-ies showed that CRP and IL-6 levels correlated with significance positively with Lp(a) levels in hemodialysis patients [16]. Lp(a) levels showed no significant correlations with glycemic control parameters nor insulin and triglyceride levels in study with diabetic patients [17]. Some authors suggest that levels of hsCRP are associated with a disorders of lipid profile such as an increase in total cholesterol, triglycerides and LDL cholesterol and lower HDL-but the mechanism is not entirely clear [18].…”
Section: Discussionmentioning
confidence: 83%
“…The first opinion was that there was a direct relationship between Lp(a) levels with TC and LDL-C and a reverse relationship between Lp(a) levels with HDL-C in healthy participants. The results from a research indicated that serum Lp(a) levels have a positive correlation with TC and LDL-C in patients with T2DM [ 16 ]. These results also revealed that serum Lp(a) levels had no significant associations with glycemic indices, HDL-C, BMI, and high blood pressure [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from a research indicated that serum Lp(a) levels have a positive correlation with TC and LDL-C in patients with T2DM [ 16 ]. These results also revealed that serum Lp(a) levels had no significant associations with glycemic indices, HDL-C, BMI, and high blood pressure [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that lipoprotein (a) {Lp (a)} levels were elevated in patients with T2D. Lipoprotein (a) is a modified LDL particle that is considered an important risk factor for cardiovascular diseases (CVDs) in diabetic patients via its proatherogenic, prothrombotic, and inflammatory properties [5].…”
Section: Introductionmentioning
confidence: 99%